EXPLORATION OF THEMES OF LOVE AND NATURE IN THE POETRY OF BYRON AND LERMONTOV - Ruzibayeva Aziza Kahramanovna (Western European Studies, 2024)
This article explores the themes of love and nature in the poetry of two prominent poets, Lord Byron and Mikhail Lermontov. Through a comparative analysis of their works, this study delves into how these two poets depict the complexities of human emotions, particularly love, and their deep connection to the natural world. By examining their use of imagery, symbolism, and literary devices, this article seeks to uncover the similarities and differences in their poetic representations of love and nature.
Keywords: Lord Byron; Mikhail Lermontov; poetry